A new approach for seasonal pattern: is it related to bipolarity dimension? Findings from an Italian multicenter study. (1st March 2021) - Aguglia, Andrea; Cuomo, Alessandro; Amerio, Andrea; Bolognesi, Simone; Di Salvo, Gabriele; Fusar-Poli, Laura; Goracci, Arianna; Surace, Teresa; Serafini, Gianluca; Aguglia, Eugenio; Amore, Mario; Fagiolini, Andrea; et al.
Abstract: Objective: The aims of this study were to assess the impact of seasonal pattern on several clinical dimensions in inpatients with a current major depressive episode and to evaluate clinical differences between unipolar and bipolar depression according to seasonal pattern. Methods: Study participants were 300 patients affected by major depressive disorder (MDD) or bipolar disorder (BD) currently experiencing a major depressive episode (MDE) and were recruited at three University Medical Centres in Italy. All study subjects completed several evaluation scales for depressive and hypomanic symptoms, quality of life and functioning, impulsiveness, and seasonal pattern. Results: Several differences between BD with and without seasonal pattern, MDD with and without seasonal pattern but in particular between BD and MDD with seasonal pattern were found. Patients with MDE with seasonal pattern had more frequently received a longitudinal diagnosis of BD. Conclusions: A large number of patients with BD and seasonal pattern, but also a considerable number of patients with MDD and seasonal pattern, endorsed manic items during a current MDE. Seasonal pattern should be associated with a concept of bipolarity in mood disorders and not only related to bipolar disorder. A correct identification of seasonal patterns may lead to the implementation of personalised pharmacological treatment approaches. KEY POINTS: High prevalence of mixed features in mood disorders with seasonal pattern, supporting the need for a dimensional approach to major depressive disorder and bipolar disorder. Significant percentage of patients with a primary diagnosis of major depressive disorder had seasonal pattern. Significant percentage of patients with a primary diagnosis of major depressive disorder reported (hypo)manic symptomatology.